IMPROVE THE RESULTS OF LEARNING FIQH LESSONS WITH THE STAD CLASS VII METHOD AT MTS KANDEPAG MEDAN PROJECT - Rijal Sabri; Lia Raudhoni (Universitas Dharmawangsa, 2021)
The teaching results that students have with each other are different, some are experiencing improvements and there are children whose results are the same. These results are used as a reference by researchers to continue research in the next cycle. It can be seen that the achievement of student learning outcomes in pre-bullying is obtained on average a percentage of 51.83%, and in Cycle I obtained an average percentage of 56.66%. So that from these two achievements can be obtained the average difference is 4.83%. The results of measurements on pretindakan and Cycle, I showed that the achievement of learning outcomes in pretindakan to Cycle I showed an increase of 4.83%. The results of measurements in Cycle II showed that the achievement of learning outcomes increased. The learning outcomes that one child has with another are different, but most children have improved. It can be seen that the achievement of children's learning outcomes in Cycle I is obtained on average a percentage of 56.66%, and in Cycle II obtained an average percentage of 86.66%.